The supplementary agreement no.02 to extend the time of completion - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the supplementary agreement no.02 to extend the time of completion of construction of foundation with basements and other civil works of BRACU new campus building.